Topography of simian virus 40 A protein-DNA complexes: arrangement of protein bound to the origin of replication. - Tegtmeyer, P (1983)
DNA binding regions I, II, and III at the origin of replication have different arrangements of A protein (T antigen) recognition pentanucleotides. The A protein also protects each region from DNase in distinctly different patterns. Footprint and fragment assays led to the following conclusions: (i) in some cases a single recognition pentanucleotide is sufficient to direct the binding and accurate alignment of A protein on DNA; (ii) the A protein binds within isolated region I or II in a sequential process leading to multiple overlapping areas of DNase protection within each region; and (iii) the 23-base pair span of recognition sequences in region II allows binding and protection of a longer length of DNA than the 23-base pair span in region I. We propose a model of protein binding that addresses the problem of variations in the arrangement of pentanucleotides in regions I and II and explains the observed DNase protection patterns. The central feature of the model requires each protomer of A protein to bind to a pentanucleotide in a unique direction. The resulting orientation of protein would protect more DNA at the 5' end of the 5'-GAGGC-3' recognition sequence than at the 3' end. The arrangement of multiple protomers at the origin of simian virus 40 replication is discussed.